2020
DOI: 10.1159/000511422
|View full text |Cite
|
Sign up to set email alerts
|

The Upper Digestive Tract Microbiome and Oesophageal Squamous Cell Carcinoma: Epidemiology, Pathogenesis, and Clinical Implications in Africa

Abstract: The study of the microbiome has significantly contributed to our understanding of complex diseases including cancer, with a profound influence of the microbiota on clinical prognosis and the efficacy of cancer treatments. Oesophageal cancer is positioned amongst the most aggressive malignant diseases, resulting from a complex interaction between anthropometric, genetic, immune response, and environmental factors. Oesophageal squamous cell carcinoma (OSCC) is the most common type of oesophageal cancer and is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 109 publications
0
1
0
Order By: Relevance
“…[24][25][26][27][28][29] Possible mechanisms of carcinogenesis include chronic inflammation in the setting of periodontal disease and/or changes in the oral microbiome leading to carcinogenic metabolite byproducts. 30 Our analysis is the first to evaluate agespecific effects of oral health on ESCC risk. We found that infrequent tooth brushing was associated with an increased risk of early-onset ESCC, whereas tooth loss had null effect.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26][27][28][29] Possible mechanisms of carcinogenesis include chronic inflammation in the setting of periodontal disease and/or changes in the oral microbiome leading to carcinogenic metabolite byproducts. 30 Our analysis is the first to evaluate agespecific effects of oral health on ESCC risk. We found that infrequent tooth brushing was associated with an increased risk of early-onset ESCC, whereas tooth loss had null effect.…”
Section: Discussionmentioning
confidence: 99%